ANALISIS ASPEK KESEHATAN LINGKUNGAN DI TEMPAT WISATA TAMAN MARGASATWA SEMARANG - Diah Fatmawati; Sulistyani Sulistyani; Budiyono Budiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Public place such as zoo has the potential for disease transmission.The purpose of this research was to analyze environmental health aspect in zoo of Semarang. This research method was descriptive research with qualitative approach. The were analyze the sanitation and personal hygiene condition such as clean water, garbage, public toilet, office space, mosque, food sanitation, animal cages, 8 food traders and 10 cages keeper. The analysis of this study was univariate. The result of this research was water supply had fulfilled the requirement equal to 67%. The condition of the sewerage channel from public facilities and from the cages had not fulfilled the requirements by 100% (14 places) and 55% (6 cages). The condition of public toilets had fulfilled the requirements by 67%. Waste management of public facilities and cages had not fulfilled the requirements. The sanitary situation of the zoo management office had fulfilled the requirements by 100%. The sanitation condition of the mosque had fulfilled the requirement by 100%. Personal hygiene food traders had fulfilled the requirements by 100%. Food sanitation was eligible at 100%. The density of flies in the zoo was rated high (an average of 18 flies). The cages keeper had not fulfilled the requirement by 100%. Animal cages sanitation had fulfilled the requirements by 92%. The size of the animal cages had not fulfilled the standard by 56%. Feeding the animals had not fulfilled the requirements by 51%. The conclusion of this research was the aspect of environmental health at Zoo Semarang was already good.